A Simplified and Selective Technique for The Direct Recovery of Glucose-6-Phosphate Dehydrogenase From Unclarified Yeast Feedstock - Chow, Yen Mei (2005)
The development of a simplified and rapid technique for the selective recovery of proteins from Bakers' yeast was undertaken. Purification of Glucose-6-phosphate dehydrogenase (G6PDH) from Saccharomyces cerevisiae was chosen demonstrate of this principle. Cell disruption is a mandatory first step in the recovery of intracellular products. The influence of the operational parameters of Dyno bead mill on the release of G6PDH and proteins study were studied, and demonstrated that 45 ~hr-' flow rate, 85% (v/v) bead volume, 10 ms" tip speed are optimum condition for protein released. The comparative study on expanded beds ion-exchange and affinity adsorbents for the purification of G6PDH from crude feed-stock was conducted. The use of Streamline DEAE (p-1.2 @-I) and Upfront Cibacron Blue 3GA (p-1.5 gmL,-') in adsorption of G6PDH from Bakers' yeast is adapted in this study. Hydrodynamic performance testing indicated that Upfront adsorbent providing a more stable fluidized bed than Streamline adsorbent does. Due to consisting higher density, higher flow rate (225 to 450 cmhf') and biomass concentration (up to 30% W/V) could be applied on expanded Upfront adsorbent bed. In contrast, Streamline adsorbent only able to afford a range of flow rate, from 164.2 to 248.3 cmhr-' and biomass concentration up to 20% wlv. For dye affinity system, there is a light reduction on dynamic binding capacity of BSA (1 1.1% to 27.8%) only as compare with ion-exchange system (43.1% to 68.6%) when the adsorption was conducted in the presence of intact yeast cells. The adsorption characteristics of the affinity system were not greatly altered in the presence of cells in contrast to the results from a less selective ion-exchange system. It was demonstrated that dye affinity chromatography had provided a higher purification factor (3.9 to 8.2) with as compared with ion-exchange chromatography (2.7 to 4.1) in G6PDH recovery.